CHALLENGES AND OPPORTUNITIES IN PREPARING PROSPECTIVE TEACHERS IN THE DIGITAL ERA: A CRITICAL STUDY BASED ON DIGITAL LITERACY PROFILE - Sele, Yunawati; Dewi, Ni Putu Yuni Astriani (Universitas Labuhanbatu, 2025)
Purpose—The preparation period for prospective teachers at the Teacher Training Institute begins with preparing them to navigate the digital era. Digital literacy is a crucial competency that needs to be effectively developed during this period. This study aimed to evaluate the opportunities and obstacles associated with preparing prospective teachers for the digital era by examining their digital literacy profiles.Methodology—This research employed a quantitative descriptive research design involving 250 students from the Faculty of Teacher Training and Education at Timor University. We conducted the research in three stages: preparation, implementation, and final. The research data, obtained through a digital literacy questionnaire, underwent quantitative descriptive analysis.Findings – The study's results indicated that prospective teachers' average digital literacy score was 73.86, with 60% of respondents falling into the